Prevalence and clinical features of patients with autoimmune pancreatitis and inflammatory bowel disease: A systematic review and meta‐analysis. Issue 8 (2nd June 2022) - Fukuda, Soma; Akiyama, Shintaro; Tarakji, Ahmad; Hamdeh, Shadi; Suzuki, Hideo; Tsuchiya, Kiichiro
Abstract: Background and Aim: Autoimmune pancreatitis (AIP) and inflammatory bowel disease (IBD) are categorized into immune‐mediated inflammatory disorders (IMIDs). While AIP is a pancreato‐biliary IMID with an increased incidence and prevalence among patients with IBD, its features are still unclear. This systematic review and meta‐analysis aims to assess the prevalence and clinical characteristics of AIP‐IBD patients. Methods: Electronic databases were searched to identify observational studies assessing AIP and IBD. The primary outcome was the prevalence of IBD among AIP patients, and vice versa. Secondary outcomes included clinical findings and outcomes of each IMID in AIP‐IBD patients. The pooled rate of each outcome was determined using a random effects model. Results: For primary outcomes, 40 observational studies with 4031 AIP patients were included and the pooled prevalence of IBD was 10.5% (95% CI 7.2–15.0%). Meanwhile, five studies with 10, 551 IBD patients were included and the pooled prevalence of AIP was 0.6% (95% CI 0.2–1.9%). For secondary outcomes, 53 observational studies with 469 AIP‐IBD patients were assessed. The rates of type 2 AIP and ulcerative colitis were 79.2% (95% CI 69.1–86.6%) and 74.8% (95% CI 68.2–80.4%), respectively. We also demonstrated AIP‐IBD patients were at a significant increased risk of AIP recurrence and colectomy compared with patients with either AIP or IBD (RR = 1.9, 95% CI 1.1–3.1 and P = 0.014 and RR = 3.7, 95% CI 1.9–6.9, P < 0.001, respectively). Conclusions: Our meta‐analysis reported the prevalence of AIP‐IBD patients and demonstrated patients with both IMIDs had a high risk of poor outcomes.